Ca2+ signaling in T lymphocytes: the interplay of the endoplasmic reticulum, mitochondria, membrane potential, and CRAC channels on transcription factor activation - Pei-Chi Yang; M. Saleet Jafri (Heliyon, 2020)
T cell receptor stimulation initiates a cascade of reactions that cause an increase in intracellular calcium (Ca2+) concentration mediated through inositol 1,4,5-trisphosphate (IP3). To understand the basic mechanisms by which the immune response in T cells is activated, it is useful to understand the signaling pathways that contain important targets for drugs in a quantitative fashion. A computational model helps us to understand how the selected elements in the pathways interact with each other, and which component plays the crucial role in systems. We have developed a mathematical model to explore the mechanism for controlling transcription factor activity, which regulates gene expression, by the modulation of calcium signaling triggered during T cell activation. The model simulates the activation and modulation of Ca2+ release-activated Ca2+ (CRAC) channels by mitochondrial dynamics and depletion of endoplasmic reticulum (ER) store, and also includes membrane potential in T-cells. The model simulates the experimental finding that increases in Ca2+ current enhances the activation of transcription factors and the Ca2+ influx through CRAC is also essential for the NFAT and NFκB activation. The model also suggests that plasma membrane Ca2+-ATPase (PMCA) controls a majority of the extrusion of Ca2+ and modulates the activation of CRAC channels. Furthermore, the model simulations explain how the complex interaction of the endoplasmic reticulum, membrane potential, mitochondria, and ion channels such as CRAC channels control T cell activation.